Monetary and Fiscal Policy Interactions in an Emerging Open Economy: a Non-Ricardian DSGE Approach - Aliya Algozhina (FIW - Research Centre International Economics, 2012)
The monetary and fiscal policy interactions have gained a new research interest after the 2008 crisis due to the global increase of fiscal debt. This paper constructs a macroeconomic model of joint fiscal and monetary policy for an emerging open economy taking into account its structural uniqueness. In particular, the two instruments of monetary policy, interest rate and foreign exchange intervention, the two instruments of fiscal policy, public consumption and public investment, the two types of households, optimizers and rule-ofthumb individuals, and a foreign debt via collateral constraint are modeled here in a single DSGE framework. The parameters are calibrated for the case of Hungary using data over 1995Q1-2011Q3. The impulse response functions to public investment, public consumption, and interest rate shocks reveal some unconventional findings in favor of the fiscal theory of price level as opposed to the traditional monetarist doctrine.
Keywords: E31; E52; E62; E63; F41; H54; H63; 330; monetary policy; fiscal policy; emerging open economy; collateral constraint; fiscal theory of price level